Was Rabbi Ovadia Yosef a Protofeminist? A Look at His Oral Sermons - Schramm, Netta (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2023)
This article examines Rabbi Ovadia's sermons, exploring his stance on women through folktales and narratives dedicated to halakhic scenario-building. Yosef's editorial intervention in a folktale by Yosef Hayyim of Baghdad is discussed, revealing his departure from the trope of woman as seducer and a shift in the status of the evil inclination. In short narratives of halakhic scenarios, Yosef prefers depicting religiously empowered "good" women. However, the subtext of these sermons is not an untheorized feminism; instead, they express Yosef's pragmatic worldview. Yosef's positive concept of the human psyche and its capacity for reason, dignity, and virtue guided his editorial decisions in severing the link between women and sin, endowing women with responsibility and agency. Yosef believed negative depictions of women as temptation's embodiment, lacking inherent religious value, harmed the religious well-being of both men and women. Thus, pragmatic considerations led him to craft narratives with reduced misogyny and gynophobia.